Manajemen Praktek Kerja Industri untuk Meningkatkan Keterserapan Lulusan SMK pada Dunia Usaha dan Dunia Industri - Ridho Iktiari; Agustina Sri Purnami (Media Manajemen Pendidikan, 2019)
The purpose of this study is to (1) find out about internship planning; (2) organization of the internship (3) Implementation of the internship; and (4) internship evaluation at Vocational School Kalasan. This research is qualitative research carried out at Vocational School Kalasan. Data collection techniques include interviews, observation, and documentation analysis. Data analysis techniques using qualitative descriptive analysis including data collection, data reduction, data display, and data verification. The results of this study: (1) internship planning at Vocational School Kalasan has been done well as in the planning stages of the activities namely curriculum synchronization, industry map making, working group coordination, socialization, and debriefing. (2) The organization of the Internship has been carried out well and is the coordination carried out by the internship committee and the public relations working unit. (3) The implementation of the internship has been carried out well in semester 4 for 3 months. The activities in the implementation of internship are: a) searching / submitting internship, b) submitting internship, c) implementation and placement of students in industry, d) monitoring internship, e) withdrawal internship, and f) reporting and assessment internship. (4) Internship evaluation in Vocational School Kalasan has been carried out well, by collecting data and analyzing the data. The evaluation was conducted in a meeting attended by the principal, vice-principal of curriculum, vice-principal of public relations, and other vice principal, and all head of departments. Each department also evaluates different activities.Â